Optimization and Stability of Total Pigments Production of Fusan from Protoplast Fusion of Microalgae Dunaliella and Chlorella in vivo: Attempts on Production of Sustainable Aquaculture Natural Food - Hermin Pancasakti Kusumaningrum; Muhammad Zainuri (International Journal of Marine and Aquatic Resource Conservation and Co-existence, 2014)
Diversification of feed rich in natural carotenoids is needed in aquaculture because they will increase survival and body weight of animal farming. Different types of important carotenoids such as β-carotene, zeaxanthine can be combined through a process of protoplast fusion making it cheaper and faster. Crustaceans can not synthetize carotenoid de novo and they need it to provide nutrition and possibly disease resistance, pigmentation and esthetic value. Green microalgae produce carotenoids and can be manipulated easily by protoplast fusion. The research was conducted to obtain some fusants from interspesies protoplast fusion of D. salina and C. vulgaris. Interspecies protoplas fusion was carried out by protoplast isolation, protoplast fusion and protoplast regeneration. Microscopic and cell analysis will used to confirm positive regenerate protoplast. Analysis of the obtained fusants is limited to morphological description due to the complexity and variability of fusant. The stabilities of fusants obtained were examined by successive subcultures. The result revealed that the fusant from D. salina and C. vulgaris maintain their stability in growth and increased carotenoid production during four periods of subculturing. This result suggesting the potency of fusant to be used as food supplement. Key words: Carotenoid, Protoplast fusion, Dunaliella, Chlorella